2016
DOI: 10.18632/oncotarget.12141
|View full text |Cite
|
Sign up to set email alerts
|

Grp94 in complexes with IgG is a soluble diagnostic marker of gastrointestinal tumors and displays immune-stimulating activity on peripheral blood immune cells

Abstract: Glucose-regulated protein94 (Grp94), the most represented endoplasmic reticulum (ER)-resident heat shock protein (HSP), is a tumor antigen shared by different types of solid and hematological tumors. The tumor-specific feature of Grp94 is its translocation from the ER to the cell surface where it displays pro-oncogenic functions. This un-physiological location has important implications for both the tumor pathology and anti-tumor therapy. We wanted to address the question of whether Grp94 could be measured as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The aim of our work was to test the possibility that PU-inhibitors could antagonize the effects driven on vascular cells by Grp94. In particular, since Grp94 following its extracellular liberation is found almost exclusively in complexes with IgG [24], we wanted to see whether PU-inhibitors, by binding to the ATP site in Grp94 could also prevent Grp94 binding to IgG. Considering the strong stability and deleterious effects driven on vascular cells by circulating Grp94-IgG complexes [21,23], prevention of the Grp94-IgG complex formation might represent a better therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of our work was to test the possibility that PU-inhibitors could antagonize the effects driven on vascular cells by Grp94. In particular, since Grp94 following its extracellular liberation is found almost exclusively in complexes with IgG [24], we wanted to see whether PU-inhibitors, by binding to the ATP site in Grp94 could also prevent Grp94 binding to IgG. Considering the strong stability and deleterious effects driven on vascular cells by circulating Grp94-IgG complexes [21,23], prevention of the Grp94-IgG complex formation might represent a better therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that both native Grp94-IgG complexes isolated from plasma of diabetic patients and surrogate complexes formed in vitro by incubating Grp94 with pre-immune IgG show qualitatively similar angiogenic-like effects on human umbilical vein endothelial cells (HUVECs) by activating differentiation-specific cellular pathways [22,23]. The finding that Grp94 in complexes with IgG has the capacity to sustain and propagate the morphological alteration on vascular cells by autocrine/paracrine mechanism [23], together with the observation that Grp94-IgG complexes circulate in plasma of cancer plasma as a marker of the disease [24] support the possibility that alterations induced by these complexes on the vasculature can contribute to the growth and dissemination of the tumor. It would be therefore of particular interest to see whether purine-scaffold compounds can either antagonize Grp94 when in complex with IgG, or prevent Grp94 binding to IgG, thus representing an useful pharmacological option for antagonizing the unwanted effects driven on the vasculature by Grp94-IgG complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a LMM can be suitable for these data. Using paired Mann-Whitney tests, Tramentozzi et al (2016) show that GRP94 in complex with IgG at the higher dose can significantly inhibit the production of IgG, whereas GRP94 at both doses can stimulate the secretion of IL-6 and TNFα from PBMCs of cancer patients. In addition, some of the differences between treatments were significant for a specific gender; see Tramentozzi et al (2016) for full details.…”
Section: Effects Of Grp94-based Complexes On Il-10mentioning
confidence: 99%
“…The GRP94 dataset (Tramentozzi et al, 2016) concerns the measurement of glucose-regulated protein94 in plasma or other biological fluids and the study of its role as a tumour antigen, i.e. its ability to alter the production of immunoglobines (IgGs) and inflammatory cytokines in the peripheral blood mononuclear cells (PBMCs) of tumour patients.…”
Section: Effects Of Grp94-based Complexes On Il-10mentioning
confidence: 99%
See 1 more Smart Citation